Observer ethical judgements across culture : the role of scope of justice and moral intensity. - Chia, Joshua Yeong Jia. (2008)
Observer’s ethical judgment was influenced by his scope if justice with resects to either the moral agent or the target person affected by the moral decision. The present study integrated these two prominent concepts in ethical decision-making. It also addressed the issue of the lack of research on ethical judgment of observers.